Prevalensi Miopia pada Siswa Sekolah Dasar di Kota Salatiga Selama Pandemi Covid 19 - Dhanang Puspita; Pulung Nugroho; Kristiawan Prasetyo Agung Nugroho; Kukuh Pambuka Putra (Universitas Kristen Satya Wacana Salatiga, 2022)
The Covid-19 pandemic requires students to study online and limit outdoor activities. Thus, students have the potential to eye problems, because the afcing duration the monitor is longer and reduced of outdoor activity. The purpose of this community service is to provide eye health education, visual test, and distribution of glasses to elementary school students. The methods; eye test, education and interviews. The results, 216 students and 38 students have eye problems and had to wear glasses. This visual problem is caused by the frequency and duration of using the cellphone for a long time. It can be concluded that all students get that minus glasses and anti-blue light glasses and eye health education.